Validity and Reliability of the Indonesia version St. George’s Respiratory Questionnaire - Nury Nusdwinuringtyas; Gunawan Kurniadi; Anita Ratnawati; Peggy Sunarjo (Indonesian Journal of Physical Medicine & Rehabilitation, 2019)
Introduction: St. George’s Respiratory Questionnaire (SGRQ) is a measuring tool to assess the quality of life of people with chronic obstructive pulmonary disease or various respiratory disorders. This study aimed to assess whether The Indonesian version of SGRQ was valid and reliable for subjects with chronic obstructive pulmonary disease (COPD). Methods: The Indonesian version of SGRQ was analyzed using a correlation test between SGRQ and sixminute walk distance (6 MWD) for validity. The reliability test was done using the test re-test reliability test by Spearman’s rank correlation, and Cronbach’s alpha for internal consistency. Results: Twenty-two patients eligible COPD patients were included in this study. There is a correlation between SGRQ’s component and 6MWD on activity (r= 0.49), impact (r= -0.58) and total SGRQ (r=-0.56). The SGRQ re-measurement test shows a strong correlation on the symptom (r = 0.76), activity (r = 0.58), impact (r = 0.51), total (r=0.58) and Wilcoxon test result shows there were no significantdifferences among subscales except total value p = 0.049. High internal Cronbach’s alpha consistency was approximately 0.73 to 0.86. Conclusion: The Activities and Impacts of Indonesian version of SGRQ component provides a picture of the validity to functional capacity. The Indonesia version of SGRQ is also proven to have good repeatability with high internal consistency.